Patient radiation dose in transcatheter arterial chemoembolization for hepatocellular carcinoma using the hybrid angiography-computed tomography - Wongsoong, Romrangsri; Suwanpradit, Petchaleeya; Chaweeruk, Pimlapat; Suksai, Sukritta; Jantarattana, Trairat; Apipunyasopon, Lukkana (The Thai Journal of Radiological Technology, 2024)
Background: X-ray guided imaging using hybrid angio-computed tomography (Hybrid Angio-CT) machine combined with an interventional radiology for transcatheter arterial chemoembolization (TACE) is a core treatment in patients with liver hepatocellular carcinoma. Although TACE is well-known in the benefits of the treatment, the consideration of the radiation risk is an important. Objective: This study aimed to determine the radiation dose and the factors that affected to the patient dose obtained from TACE for hepatic carcinoma (HCC)at King Chulalongkorn Memorial hospital. Materials and Methods: The patients over 18 years old who underwent treatment of HCC using TACE in conjunction with X-ray imaging guidance from a Toshiba Hybrid Angio-CT were enrolled in this study retrospectively. We gather fluoroscopy time (FT), total acquisition time (TAT), total number of images, and dose area product (DAP) data from two-dimensional (2D) angiography, as well as dose length product (DLP) and effective dose (ED) information from three-dimensional (3D) CT scans. Results: From a total of 56 patients, we found that the median value of total ED (2D ED + 3D ED) for patients with HCC at 1-3 sites and more than 3 sites were 41.72 and 29.88 mSv, respectively. The median values of DAP closely approximate the national diagnostic reference levels (NDRLs) for TACE combined with 2D and 3D X-ray imaging. The increase in FT and TAT leads to higher 2D ED and DAP, with no observed correlation between FT or total ED and the number of HCC cancer nodules treated. Conclusion: The total ED from TACE using the Hybrid Angio-CT machine is higher than in previous research, while the DAP aligns the NDRLs for TACE combined 2D and 3D X-ray imaging.